The features of Chinese students’ integration into the learning environment of Russian universities - M. A. Galaguzova; A. V. Shvetsova; Wei Zhang (Образование и наука)
Introduction. At the cultural and symbolic level, admitting foreign students helps promote Russian education on a global scale and fosters interethnic dialogue, translating it into tangible actions. This appears to be a significant task on Russia’s current foreign policy agenda. Aim. The present research aimed to identify the main motives of Chinese youth for studying at Russian pedagogical universities, the basic barriers to integration, as well as a subjective assessment of the prestige of Russian pedagogical education. Methodology and research methods. The methodological framework of this study is based on the synthesis of systemic and institutional approaches. To collect data, an online survey adapted to various levels of Russian language proficiency was used. Results. It has been established that Chinese students highly value the prestige of a Russian diploma and the quality of education. The language barrier has a significant impact on the quality of education, as well as on the positive evaluation of the university environment and the embrace of cultural norms. Scientific novelty. An empirical toolkit has been developed and tested to describe the features of the integration of Chinese students into the Russian educational space. The data presented enabled the authors to gain a primary snapshot of information regarding the motives, practices, and barriers faced by foreign students studying in Russia. Practical significance. The main language difficulties faced by Chinese students that hinder their successful integration into the Russian educational environment have been identified. Based on this research, there are plans to publish a Chinese-Russian and Russian-Chinese dictionary focusing on pedagogy.